2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.243
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to E-Government Education Minitrack

Abstract: The aim of this paper is to introduce the mini-track on Electronic Government Education organized as part of the Electronic Government Track at the 47 th Hawaii International Conference on System Sciences . I. RATIONALESuccessful execution of Electronic Government (EGOV) initiatives requires collaboration from a variety of stakeholders, each playing a certain role and bringing their experience and knowledge to fulfill this role. However, such stakeholders must have a common understanding of the transformative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Online surveys are becoming popular because of their flexibility, wider geographic reach, and cost effectiveness [8]. Online surveys also enable efficient resource use and are more likely lead to lower missing values and faster response time compared to mail surveys [16].…”
Section: Data Collectionmentioning
confidence: 98%
See 2 more Smart Citations
“…Online surveys are becoming popular because of their flexibility, wider geographic reach, and cost effectiveness [8]. Online surveys also enable efficient resource use and are more likely lead to lower missing values and faster response time compared to mail surveys [16].…”
Section: Data Collectionmentioning
confidence: 98%
“…This in turn requires raising awareness and interest among academic partners to offer training and educational programmes [16] [8]. Initial steps in this direction were already undertaken as e-Government researchers identify sets of knowledge areas and skills that are likely to lead to GCIO's success [3]…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As an area of research, e-Government education only gained momentum in recent years. The culmination of this sub-field in e-government research may be attributed to the launch of the Electronic Government Education Mini-Track at the Hawaii International Conference on System Science in 2013 and 2014 (Estevez et al, 2014;Janowski, Cellary, & Davies, 2013). The papers in this Mini-Track suggested that the focus on fundamental issues as reflected in earlier works are no longer prominent.…”
Section: E-government Educationmentioning
confidence: 99%
“…Some of the oft cited challenges faced by developing countries include inadequate information infrastructure, poor leadership and weak governance, as well as a lack of human and knowledge capital. In fact, studies have pointed to the importance of knowledgeable and skilled public servants and citizens in achieving e-government success (Dawes & Pardo, 2002;Estevez, Cellary, & Davies, 2014;Edelmann, Parycek, & Schossbock, 2013;Humnius & Schippen, 2013). Even though the need for excellent e-government training programs has often suggested to address such knowledge deficiency (Edelmann et al, 2013;Humnius and Schippen, 2013), a scan of the literature revealed a lack of insights on how an effective e-government training program targeting government executives and citizens can be developed.…”
Section: Introductionmentioning
confidence: 99%